Determination of Potential Pelagic Fishing Ground Based on Chlorophyll a Using Aqua Modis Satellite - Sitorus, Hotma Stefany; Manu, Lusia; Kaparang, Frangky E; Dien, Heffry V (Sam Ratulangi University, 2022)
The purpose of this study was to determine the potential pelagic fishing ground using Aqua Modis satellite imagery in WPP 716. Catch data and coordinates of fishing ground from September to November 2021 were taken from the Tumumpa Fisheries Port, Manado. Chlorophyll-a data and Sea Surface Temperature data were downloaded from the website of http://oceancolorgsfc.nasa.gov. The results showed that the distribution of chlorophyll-a was concentrated at 02011'982